2011
DOI: 10.1002/ird.610
|View full text |Cite
|
Sign up to set email alerts
|

The African market garden: The development of a low‐pressure drip irrigation system for smallholders in the sudano sahel

Abstract: The African Market Garden (AMG) is a holistic horticultural production system for small producers based on low-pressure drip irrigation combined with a crop management package. Over the last 10 years, ICRISAT (the International Crops Research Institute for the Semi-Arid Tropics) and partners have tested four AMG models in the Sudano Sahel of West Africa. The Thrifty (80 m 2 ) and Commercial (500 m 2 drip kit) AMG systems were developed for individual gardening. The Cluster (multiple kits of 500 m 2 ) and Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
0
27
0
2
Order By: Relevance
“…In many interventions, a communitarian management of the irrigation perimeters is required and promoted by the international donors [12]. One of the main adduced motivations is that, by decentralizing to local institutions the management of water resources, the whole community will benefit, and this will lead to a sustainable use of the resources over time [40].…”
Section: Farmer Organizations and Gender Exclusion Mechanismsmentioning
confidence: 99%
“…In many interventions, a communitarian management of the irrigation perimeters is required and promoted by the international donors [12]. One of the main adduced motivations is that, by decentralizing to local institutions the management of water resources, the whole community will benefit, and this will lead to a sustainable use of the resources over time [40].…”
Section: Farmer Organizations and Gender Exclusion Mechanismsmentioning
confidence: 99%
“…Its promoters argued this success was linked to the suitability of the micro-drip technology for the specific arid environment of the Sahel and its affordability for smallholder farmers (Pasternak et al 2006;Woltering, Pasternak, and Ndjeunga 2011). In several other countries of Sub-Saharan Africa (Kenya, Zimbabwe, and South Africa), micro-drip kits were likewise said to have been successfully introduced for small-scale vegetable gardening (Kabutha, Blank, and van Koppen 2000;Karlberg et al 2007).…”
mentioning
confidence: 99%
“…Through follow-up visits to farmers who purchased the pumps, KickStart estimates that their pumps have created $110 million in new wages and profits and have helped move more than 600,000 individuals out of poverty. Baseline surveys have confirmed that most farmers are selling their products locally, providing more evidence for the large (and elastic) local demand for vegetables and fruits that are often high in micronutrients (23,27).…”
Section: Brief Historical Developmentmentioning
confidence: 99%
“…Over the last decade, the International Crops Research Institute of the Semi-Arid Tropics (ICRISAT-Niger) has helped install thousands of "African Market Gardens" (AMGs)-a holistic irrigation and management package-in nine countries across the Sudano-Sahel region of West Africa (27,28). These systems ranged in size from 80 to 500 m 2 (for individual farmers) and up to several hectares in communal and cluster configurations.…”
Section: Brief Historical Developmentmentioning
confidence: 99%
See 1 more Smart Citation